Risk of ocular manifestations in patients with giant cell arteritis: a nationwide study in Sweden. (2nd November 2017) - Ji, J; Dimitrijevic, I; Sundquist, J; Sundquist, K; Zöller, B
Abstract : Objective : No large-scale nationwide study has determined the risk of ocular manifestations in patients with giant cell arteritis (GCA). The aim was to study the incidence and risk factors of ocular manifestations in patients with GCA in Sweden. Method : A national cohort was created by linking Swedish nationwide registers. GCA patients were identified from the Swedish Hospital Inpatient and Outpatient Registers between 2002 and 2010, and were followed until the development of ocular manifestations. Standardized incidence ratios (SIRs) and 95% confidence intervals (CIs) were calculated for ocular manifestations in patients with GCA compared to those without GCA. Results : We identified 3737 males and 8311 females with GCA. A total of 1618 individuals had subsequent ocular manifestations, representing 13.4% of the GCA patients. The overall SIR of ocular manifestations was 6.96 (95% CI 6.63–7.31). The risk for disorders of the optic nerve or visual tract was particularly high (SIR = 51.68, 95% CI 46.12–57.73). Men with GCA had a higher risk than women, and GCA patients without polymyalgia rheumatica (PMR) symptoms had a higher risk than those with PMR symptoms. Living outside big cities was negatively associated with ocular manifestations in GCA patients, whereas hypertension and diabetes were associated with an increased risk of ocular manifestations. Conclusion : The overall risk of ocular manifestations was higher in GCA patients than in the general population, especially for men and for those without PMR symptoms.